1982
DOI: 10.1029/ja087ia01p00181
|View full text |Cite
|
Sign up to set email alerts
|

The diurnal variation of atmospheric sodium

Abstract: Continuous measurements of the vertical distribution of atmospheric sodium, made over a number of complete diurnal cycles, show the existence of strong semidiurnal oscillations in total abundance and height. The amplitude of the abundance variation, about 15% of the mean, is about twice that predicted for the 2,2 mode of the semidiurnal tide, and its phase, with maxima at 0400 and 1400 LT, is in good agreement with tidal theory. The vertical oscillation, with an amplitude of 2 km at a height of 100 km, is abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 13 publications
2
48
1
Order By: Relevance
“…4c, there is now less than 0.5 km change in the peak height between midnight and midday. In contrast, the centroid height of the layer decreases from 92.5 km to 91.0 km in daytime, which is in good accord with observations (Clemesha et al, 1982). This decrease arises largely because during daytime there is additional ionization of Na on the topside, as well as photolysis of NaHCO 3 on the bottomside.…”
Section: Meteoroid Ablation Modelsupporting
confidence: 80%
See 2 more Smart Citations
“…4c, there is now less than 0.5 km change in the peak height between midnight and midday. In contrast, the centroid height of the layer decreases from 92.5 km to 91.0 km in daytime, which is in good accord with observations (Clemesha et al, 1982). This decrease arises largely because during daytime there is additional ionization of Na on the topside, as well as photolysis of NaHCO 3 on the bottomside.…”
Section: Meteoroid Ablation Modelsupporting
confidence: 80%
“…This shows that the Na layer always peaks below 90 km, that the peak moves 2 km lower in daytime, and that the underside of the layer has a scale height less than 1 km. These model predictions are not in accord with lidar observations of the diurnal behaviour of the layer (Clemesha et al, 1982;States and Gardner, 2000). However, if removal of NaHCO 3 by dimerization is now switched on in the model, Fig.…”
Section: Meteoroid Ablation Modelcontrasting
confidence: 35%
See 1 more Smart Citation
“…5c) with lidar measurements made in Brazil at this latitude. These measurements show a predominantly semi-diurnal variation with maxima at 06:00 and 18:00 LT (Clemesha et al, 1982). However, these lidar observations were restricted to winter, whereas the satellite measurements exhibit the relatively modest diurnal variation at 23 • S during spring and autumn, and in fact show essentially no diurnal variation at the summer solstice (January).…”
Section: Diurnal Variation In the Equatorial Regionmentioning
confidence: 90%
“…The distribution of our measurements compared to any tidal variation happened to be rather even, so that any tidal variation would change the mean and median values only by a small amount. We see that the Na column density is subject to variation, but according to Granier and Mégie (1982) and Clemesha et al (1982) the Na layer does not exhibit a significant diurnal variation. Plane (2004) has shown that the lack of a diurnal variation of the Na layer can be caused by the uptake of NaHCO 3 (the major Na reservoir species below about 85 km) on meteoric smoke particles.…”
Section: Sodium Layermentioning
confidence: 95%